Gulf steamer, Warwick Bay, Trinidad - (:unkn) unknown (Unknown, 2011)
The postcard shows a steamer in Warwick Bay, Trinidad.
Colour: Coloured; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Steamboats--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago)